PATANI MALAY PHATIC EXPRESSION - Ogya Andhika Al Falah; Atsauriy , M. Jamal Aldin Al Afqhoni; Adul Sapae-ing; Ridho Firmanda Akbar; Redika Cindra Reranta (Linguistics and Literature Journal, 2025)
This study examines the significance of phatic expressions in Patani Malay speech as part of communicative practices that reflect the social and cultural identity of its speakers. This research aims to describe the variations of phatic forms and their pragmatic functions in daily interactions, particularly how particles such as ka, dok, la, weh, po, keh, and deh are utilized to maintain conversational harmony and mark interpersonal closeness. This study employed a qualitative descriptive method with data collection techniques comprising in-depth interviews with Patani Malay people. The obtained speech data were analyzed syntactically and pragmatically to uncover patterns of phatic usage within natural communication contexts. The results indicate that phatic expressions in the Patani Malay dialect exhibit variations in form, encompassing single particles, short phrases, and brief clauses that function flexibly to soften utterances, convey light emotions, and maintain social relationships. These findings further reveal that phatic particles play a crucial role in mitigating Face-Threatening Acts (FTAs), refining speech, and ensuring that conversations proceed cooperatively. This study concludes that the use of phatics serves as a linguistic strategy that affirms the values of politeness, solidarity, and the cultural identity of the Patani community. Keywords: interpersonal communication, Patani Malay dialect, phatic expressions, politeness strategies, pragmatic functions